Challenges to the integration of circular economy into the strategic management of the agricultural sector: A systematic review (SCIÉNDO INGENIUM, 2025)
The circular economy is emerging as a key strategy for achieving sustainability in the agricultural sector, given its dependence on natural resources and its environmental impact. This study aims to systematically analyze the scientific literature on the incorporation of circular economy into agricultural sector management, using the strategic direction approach as an analytical framework. The PRISMA protocol was used for the systematic review of 35 scientific papers selected from international databases. Bibliometric and thematic analysis was conducted using R Studio, which allowed for the identification of trends, co-occurrence networks, and research gaps. The results show a progressive growth in publications related to the circular economy in agricultural companies, with a predominance of studies focused on environmental and internal process perspectives, while financial and organizational learning dimensions are less addressed. It is concluded that implementing CE in the agricultural sector requires a comprehensive strategic approach that articulates sustainability and organizational performance indicators, such as investment in R&D for green technologies and innovation in patents. This study contributes a useful conceptual framework for researchers, policymakers, and agroindustrial managers
Keywords: Sustainability; innovation; environmental management; resource transformation